"УЛС ТӨРИЙН ШИНЖЛЭХ УХААНЫ ҮНДЭС" ХИЧЭЭЛИЙН ХӨТӨЛБӨР, ЗААХ АРГА ЗҮЙН ШИНЭЧЛЭЛ - Д.Оюунчимэг (Politology, 2023)
Currently, the curriculum reform is taking place intensely at the National University of Mongolia. This process of improving curriculum demands a comprehensive set of work on effectively introducing critical thinking methods in teaching and curriculum development. improving teacher-students' involvement in teaching process and rationalizing students assessment. The pragmatic theory of learning. critical thinking. its importance and methodology of creating the skill are mentioned in the article.